Helena Blum (1904-1984) — a Polish art historian in the gender gap - Marta Smolińska (Journal of Art Historiography, 2023)
Helena Blum (1904–84) was one of the most influential Polish art historians, working both as a curator at the National Museum in Cracow and as a researcher at the Institute of Art History at the University of Wrocław. In 1922, she began studying art history and archeology at the University in Lviv. Ten years later, Blum received his doctorate from this university. This was the first dissertation on modern art in Poland. In the 1930s she also studied in France. Blum was one of the key figures in Polish art history after the Second World War. Although she never became director of the National Museum in Kraków, as curator she built up the collection of Polish art in that museum, which was very much influenced by her own taste. Her distinctive curatorial strategies and art criticism influenced the so-called canon of Polish art from 1800 to 1970.